Atrioventricular conduction in patients undergoing pacemaker implant following self‐expandable transcatheter aortic valve replacement. Issue 7 (29th April 2019) - Ghannam, Michael; Cunnane, Ryan; Menees, Daniel; Grossman, Michael P.; Chetcuti, Stanley; Patel, Himanshu; Deeb, Michael; Jongnarangsin, Krit; Pelosi, Frank; Oral, Hakan; Latchamsetty, Rakesh
Abstract: Background: Heart block requiring a pacemaker is common after self‐expandable transcatheter aortic valve replacement (SE‐TAVR); however, conduction abnormalities may improve over time. Optimal device management in these patients is unknown. Objective: To evaluate the long‐term, natural history of conduction disturbances in patients undergoing pacemaker implantation following SE‐TAVR. Methods: All patients who underwent new cardiac implantable electronic device (CIED) implantation at Michigan Medicine following SE‐TAVR placement between January 1, 2012 and September 25, 2017 were identified. Electrocardiogram and device interrogation data were examined during follow‐up to identify patients with recovery of conduction. Logistic regression analysis was used to compare clinical and procedural variables to predict conduction recovery. Results: Following SE‐TAVR, 17.5% of patients underwent device placement for new atrioventricular (AV) block. Among 40 patients with an average follow‐up time of 17.1 ± 8.1 months, 20 (50%) patients had durable recovery of AV conduction. Among 20 patients without long‐term recovery, four (20%) had transient recovery. The time to transient conduction recovery was 2.2 ± 0.2 months with repeat loss of conduction at 8.2 ± 0.9 months. On multivariate analysis, larger aortic annular size (odds ratio: 0.53 [0.28–0.86]/mm, P = 0.02) predicted lack of conduction recovery. Conclusions: Half of the patients undergoing CIED placement for heart block following SE‐TAVR recovered AV conduction within several months and maintained this over an extended follow‐up period. Some patients demonstrated transient recovery of conduction before recurrence of conduction loss. Larger aortic annulus diameter was negatively associated with conduction recovery.